Answer:
fhgiignngmtotmtjfntktngigmtkgitmrjrnrkr28395027
Step-by-step explanation:
jejf ygm no fmfijfpnfimf
Answer:
A: (0,0), B: (3, -4), 5 units
Step-by-step explanation:
A: (0,0), B: (3, -4)
To find the distance, use the distance formula. Square-root((0-3)^2+(0-(-4))^2) ---> Square-root((-3)^2 + 4^2) ---> Square-root(9+16) ---> Square-root(25) ---> 5units.
Answer: Choice C
h(x) = -x^4 + 2x^3 + 3x^2 + 4x + 5
===========================================
Explanation:
When reflecting the function f(x) over the y axis, we replace every x with -x and simplify like so
f(x) = -x^4 - 2x^3 + 3x^2 - 4x + 5
f(-x) = -(-x)^4 - 2(-x)^3 + 3(-x)^2 - 4(-x) + 5
f(-x) = -x^4 + 2x^3 + 3x^2 + 4x + 5
h(x) = -x^4 + 2x^3 + 3x^2 + 4x + 5
Note the sign changes that occur for the terms that have odd exponents (the terms -2x^3 and -4x become +2x^3 and +4x); while the even exponent terms keep the same sign.
The reason why we replace every x with -x is because of the examples mentioned below
-----------
Examples:
The point (1,2) moves to (-1,2) after a y axis reflection
Similarly, (-5,7) moves to (5,7) after a y axis reflection.
As you can see, the y coordinate stays the same but the x coordinate flips in sign from negative to positive or vice versa. This is the direct reason for the replacement of every x with -x.
She can travel 3000 miles
Answer: 15
Step-by-step explanation:
x = one point shots
y = two point shots
1) Setup your equations.
x + y = 52
x + 2y = 89
2) Isolate a variable.
x = 52-y
3) Plug in.
(52-y) + 2y = 89
52 +y =89
y=37
4) Solve for x.
x = 52 -37
x=15
5) Check your answer.
15 + 2(37) = 89
15+74=89
89=89
37+15 = 52
52=52
x = one point shots
y = two point shots
1) Setup your equations.
x + y = 52
x + 2y = 89
2) Isolate a variable.
x = 52-y
3) Plug in.
(52-y) + 2y = 89
52 +y =89
y=37
4) Solve for x.
x = 52 -37
x=15
5) Check your answer.
15 + 2(37) = 89
15+74=89
89=89
37+15 = 52
52=52